Biomarkers in IgA nephropathy: relationship to pathogenetic hits. (November 2013) - Hastings, Margaret Colleen; Moldoveanu, Zina; Suzuki, Hitoshi; Berthoux, Francois; Julian, Bruce A; Sanders, John T; Renfrow, Matthew B; Novak, Jan; Wyatt, Robert J
Abstract : Introduction: IgA nephropathy, the most prevalent glomerular disease in the world, requires a renal biopsy for diagnosis. Reliable biomarkers are needed for the non-invasive diagnosis of this disease and to more fully delineate its natural history and risk for progression. Areas covered: In this review, the authors examine serum levels of galactose-deficient IgA1 (Gd-IgA1) and glycan-specific IgG and IgA autoantibodies that are integral to pathogenesis of IgA nephropathy. They also explore biomarkers related to alternative and lectin pathways of complement activation and serum and urinary peptide biomarkers detected by mass spectrometric methods. The literature search included review of all publications having IgA nephropathy in the title that were cited in PubMed and Scopus over the past 10 years and a non-systematic review of abstracts published for the annual meetings of the American Society of Nephrology and the International Symposia on IgA Nephropathy. Expert opinion: Serum Gd-IgA1 level and glycan-specific autoantibody levels are prime candidates to become diagnostic biomarkers for IgA nephropathy because of their central role in the earliest stages of disease pathogenesis. Assays for serum levels of complement proteins C3 and factor H are readily available in clinical practice and deserve continued study, either alone or in tandem with total serum IgA or serum Gd-IgA1 levels, as prognostic biomarkers for patients with IgA nephropathy. Urinary peptidomic data are also reviewed because this approach can successfully differentiate patients with IgA nephropathy from healthy controls and from patients with other forms of renal disease.